Effects of increasing the volume of a rainwater storage tank on the territory of Poland with average rainfall - Ludwińska, Agnieszka; Dudkiewicz, Edyta (Instal, 2024)
In the case of the use of rainwater for domestic and gardening purposes in a single-family house, the capacity of rainwater, depending on the chosen calculation method, can be range from 5,000 l to 15,000 l. The threefold difference requires consideration of the benefits and effects of using tanks with different capacities. The paper analyses the performance of eleven rainwater storage tanks with different capacities depending on rainfall distribution and six profiles of rainwater distribution dynamics in a single-family house. The key is the inclusion of lawn watering or its absence. An innovative approach is the hourly step analysis, which showed that each 1,000 litre increase in tank capacity allows for an increase in water yield of 1 to 5%. The percentage of recovered rainwater in the total rainwater demand for the domestic and gardening purposes increases from 66% to 83%. Rainwater demand only for washing and toilet flushing can be fully covered by using a tank with a capacity of 6,000 l.